"Like precious gold": Recreation in the lives of low-income committed couples. (1st January 2018) - Moore, Annette C.; Henderson, Karla A.
ABSTRACT: Financial stress can heighten pressure and conflict within couple relationships. Recreation participation has the potential to alleviate stress and deepen relational bonds. Drawing on data from semistructured interviews with 25 couples, this study explores recreation in the lives of low-income couples in committed relationships. Qualitative methods were used to examine the recreation activities couples engaged in, with whom, and where; what value they placed on their recreation participation; and what factors influenced their recreation engagements. Findings indicate couples engage in a wide range of shared couple recreation, including partner-support, utilitarian, home-based, and "date-like" experiences. Couples value their recreation for both immediate and more lasting benefits and often make intentional efforts to enrich their relationships by pursuing low- or no-cost activities and by negotiating the various challenges associated with their limited financial resources. Implications for future research and practice are discussed.